2010
DOI: 10.1111/j.1365-294x.2010.04635.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter-specific gene flow dynamics during the Pleistocene-dated speciation of forest-dependent mosquitoes in Southeast Asia

Abstract: Tropical forests have undergone repeated fragmentation and expansion during Pleistocene glacial and interglacial periods, respectively. The effects of this repeated forest fragmentation in driving vicariance in tropical taxa have been well studied. However, relatively little is known about how often this process results in allopatric speciation, since it may be inhibited by recurrent gene flow during repeated secondary contact, or to what extent Pleistocene-dated speciation results from ecological specializati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 60 publications
4
45
2
Order By: Relevance
“…The start time of population expansion under the sudden expansion model was estimated using the same mutation rate as in earlier studies to enable a direct comparison with previous estimates for a single NE Indian population of An. baimaii [5,20]. However, since there is no calibrated rate for Anopheles , the estimated expansion time should be considered as very approximate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The start time of population expansion under the sudden expansion model was estimated using the same mutation rate as in earlier studies to enable a direct comparison with previous estimates for a single NE Indian population of An. baimaii [5,20]. However, since there is no calibrated rate for Anopheles , the estimated expansion time should be considered as very approximate.…”
Section: Resultsmentioning
confidence: 99%
“…baimaii in NE India has undergone expansion, a mismatch distribution was calculated in Arlequin 3.1 and compared with the expectations of the sudden expansion model. The time of expansion was estimated under the sudden expansion model assuming the mutation rate of 1.15 × 10 -8 /site/year as used by Morgan et al [5] and a generation time of 0.1 years reported for Anophelines (Maharaj, 2003) [46]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies found a significant influence from the Pleistocene glaciation on genetic diversity, genetic structure, and demographic history in many Southeast Asian floras and faunas [e.g., [21][22][23]]. During the Pleistocene glaciations, climatic and environmental conditions in Southeast Asia were cooler and drier [24].…”
Section: Discussionmentioning
confidence: 99%